NARRATIVES OF CRISIS: REPRESENTING CAPITALIST REALISM : PART II: THE GREEK CRISIS - Petsini, Penelope (Design/Arts/Culture, 2024)
Bringing together researchers, theorists and visual artists, the fourth volume of DAC journal, "Narratives of Crisis: Representing Capitalist Realism", aims to provide a platform for discussions and research, which consider various aspects of the visual and its implication to both ideological formations and cultural forms related albeit not limited to the notion of crisis. The special issues (4:1, 4:2) are, in a way, a continuation of previous, relatively recent projects which the guest editor, Dr Penelope Petsini, has curated or organised, and all invited contributors have been involved in: The group exhibitions "Capitalist Realism: Future Perfect" and "Capitalist Realism: Past Continuous" (2018-19, held at MOMus-Thessaloniki Museum of Photography and MOMus-Center of Experimental Arts, respectively), the eponymous book (University of Macedonia Press, 2018), as well as the conference "Representing Capitalist Realism: Crisis, Politics and the Visual" (23-24/11/2018, MOMus-Thessaloniki Museum of Photography & Rosa Luxemburg Foundation). Starting from this point, the issues aim to offer a comparative charting of the crisis discourse by adopting an inclusive definition of the term derived from new scholarship and the concept of "Capitalist Realism" as introduced by British theorist Mark Fisher: an ideological framework for perceiving capitalism’s impact on politics, economics, and collective consciousness – encompassing both the spheres of economy and culture. Crucially, Capitalist Realism encapsulates the prevalent notion that not only is capitalism the sole feasible political and economic structure, but it has also become nearly inconceivable to imagine a coherent alternative. Part Two ("The Greek Crisis") is a collection of essays and visual explorations which present the multifaceted dimensions of the Greek Crisis, weaving together threads of cinema, art, literature, architecture, politics, and urban life. It includes articles, visual essays, portfolios and a review by: ​Anna Poupou; Nikolas Ventourakis; Depression Era collective; Paraskevi Kertemelidou; Maria Paschalidou; Maria Moira; Io Chaviara; Ioanna Barkouta; Yannis Karpouzis - Yorgos Karailias - Yorgos Prinos - Pavlos Fysakis (Grossraum); Myrto Marini; Dimitris Kechris.